Detection and identification of lactic acid bacteria isolated from rotten vegetables - Yusof, Mu'az (2015)
Lactic Acid Bacteria (LAB) are the crucial bacteria that play important roles in the production of the fermented foods and also act as probiotic for the human when consume in adequate amounts of the bacteria. Some of the LAB also can caused harmful effects to human such as the species from the genus of Weissella sp. This research was performed in order to isolate and identify the LAB from the rotten vegetables. All of the isolated bacteria from Capsicum, Lettuce, Brinjal, Eggplant and Tomato were undergo gram stain, biochemical test, DNA purification and also gel electrophoresis. Most of the isolates inhabited by the LAB from the genus of Lactobacillus sp., only isolate form Capsicum 2 are from the genus of Streptococcus sp. All of the isolates were gram positive bacteria and the DNA extracted from all of the isolates were in size of less than 1.5 kb which were observed by using 1.5 kb ladder.